Independence and national identity in Ecuador: An approach from the work of Michael Foucault - Pardo Moreno, Pablo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Ecuadorian historiography includes three ways of interpreting the process of independence and foundation of Ecuador. Among them is the patriotic school, the materialist and the so-called Atlantic school. The devices in Foucauldian thought can be institutions, norms, laws, discourses, or simply positions regarding transcendental historical issues. These devices are not the property of a specific political subject; on the contrary, they have the capacity to constitute or strengthen those subjects. The devices found with the greatest influence in the historiography of independence are the educational system and the independence commemorations.